A detailed hydrothermal investigation of a helical micro double-tube heat exchanger for a wide range of helix pitch length. (December 2021) - Abu-Hamdeh, Nidal H.; Alsulami, Radi A.; Rawa, Muhyaddin J.H.; Aljinaidi, Abdulmalik A.; Alazwari, Mashhour A.; Eltaher, Mohamed A.; Almitani, Khalid H.; Alnefaie, Khaled A.; Abusorrah, Abdullah M.; Sindi, Hatem F.; Goodarzi, Marjan; Safaei, Mohammad Reza
Abstract: The present study was numerically inquired the heat transfer performance and fluid flow characteristic of a helical micro double-tube heat exchanger (HMDTHX) using the finite volume method. The tube length was considered to be constantly equal to 30 mm, and 12 different configurations were modeled by changing in turn number and pitch length (P) for Reynolds numbers of 50, 100, 150, and 200. The findings indicated that the heat transfer would enhance by applying any helix angle in the straight tube. However, it had an optimum point which varied by Reynolds number (Re). Rising Re caused overall heat transfer coefficient (OHTC), pressure drop, and pumping power augment for all cases. Increasing P in overall reduced OHTC, pressure drop, and pumping power which had different maximum points between P = 0.5 to 3. Maximum overall heat transfer coefficient (OHTC) enhancement was equal to 45% for Re = 200 and P = 2. Also, maximum effectiveness was 11.5% for P = 2 and Re = 200. Moreover, a 42% maximum increment was achieved for pressure drop, pumping power, and friction factor at Re = 200 and P = 2. Shear stress for Re = 100 to 200 showed that the values are almost the same for P = 0.5 and 1. Then by increasing P, the shear stress decreases. While, for Re = 50, a maximum is seen at P = 2. The temperature distribution was indicated that the maximum temperature of the straight tube and helical tube are the same, but the difference is in the average temperature, which was 3.2 K between straight and helical tubes. Finally, by investigating the velocity contour, it was determined that a secondary flow through the HMDTHX, affected by centrifugal force, was existed, enhancing the fluid flow turbulency and heat transfer rate.